2013
DOI: 10.1108/rsr-03-2013-0015
|View full text |Cite
|
Sign up to set email alerts
|

Academic libraries in the age of MOOCs

Abstract: Purpose – The article aims to report on the current development of Massive Open Online Courses (MOOCs), explore the strengths and weaknesses of MOOCs, and reflect on the possible relationships between academic libraries and MOOCs. Design/methodology/approach – The paper is based on a mix of literature review (mostly current news) and personal observations. The author discusses the unique characteristics of MOOCs, speculates on the benefits of MOOCs on higher education, and explores the impact of MOOCs on acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 1 publication
(4 reference statements)
0
13
0
7
Order By: Relevance
“…The 'Environmental Scan' report suggested that libraries should remain involved in the development and delivery of MOOCs. Similarly, Kerry Wu 11 explored the impact of MOOCs on academic libraries, and appealed academic librarians that they should be fully engaged in the discussion and action on their own campus related to MOOCs. With rapid increase in MOOC, the academic libraries have an opportunity to develop packages/portals that provide access to 'course-based additional resources' or 'e-content packages' for MOOC learners.…”
Section: Trend Predicted: Integration Of Online Hybrid and Collaboramentioning
confidence: 99%
“…The 'Environmental Scan' report suggested that libraries should remain involved in the development and delivery of MOOCs. Similarly, Kerry Wu 11 explored the impact of MOOCs on academic libraries, and appealed academic librarians that they should be fully engaged in the discussion and action on their own campus related to MOOCs. With rapid increase in MOOC, the academic libraries have an opportunity to develop packages/portals that provide access to 'course-based additional resources' or 'e-content packages' for MOOC learners.…”
Section: Trend Predicted: Integration Of Online Hybrid and Collaboramentioning
confidence: 99%
“…Otro punto a destacar es que, en la última década, muchas universidades de todo el mundo han comenzado a ofrecer Cursos Masivos Abiertos en Línea (más conocidos como MOOC) junto a su oferta formativa tradicional, lo que permite cambios en la práctica docente y el modelo de negocio de las diferentes universidades; de acuerdo con Wu (2013) "si los MOOC van a transformar a la Educación Superior, esto tendrá indudablemente un impacto significativo en la forma en que las bibliotecas trabajan y en el rol que desempeñan en el futuro del aprendizaje" (p. 85). La situación actual del campo de la cooperación de bibliotecas -MOOC, según Barnes (2013), se caracteriza por la existencia de pocos estudios, debido a lo reciente del fenómeno; al mismo tiempo, es evidente que se trata de un tema que suscita gran interés en el mundo profesional, como se puede comprobar por la celebración de eventos tales como: MOOCs and Libraries: Massive Opportunity or Overwhelming Challenge?…”
Section: Introductionunclassified
“…As the scholarly communication landscape evolves, and explores the creation and use of open resources, libraries can assist in shaping and furthering the discussions of these materials on their campuses. The careful collection, creation, and curation, of open access resources, and the subsequent marketing of these sources can aid in this work (Mitchell & Chu, 2014;Wu, 2013;Martin, 2010 (Martin, 2010). It can be a challenge to identify appropriate content, and librarians must be knowledgeable of the difference between various open access sources, and be aware of strategies for identifying relevant materials.…”
Section: Open Access Open Educational Resources and Librariesmentioning
confidence: 99%
“…As libraries are often considered the experts in copyright and licensing, a librarian may be asked to provide insight into these areas, or be asked to secure permissions for use of a particular set of resources. S/he might also be asked to provide instruction on how to find relevant and accessible sources on a topic or on a specific aspect of the research process (Barnes, 2013;Wu, 2013). Mahraj (2012) posits that librarian involvement in MOOCs follows logically from the work currently performed by librarians in the support of courses and students, and suggests that just as librarians are currently embedded in many online courses, they should also be embedded in MOOCs.…”
Section: Library Support For Moocsmentioning
confidence: 99%